Knowledge, Attitude, and Practice Towards Rehabilitation in Patients with Breast Cancer: A Cross-Sectional Study - Zhou Y; Lu Q; Yu X (Journal of Multidisciplinary Healthcare)
Yan Zhou,1,* Qin Lu,2,* Xuequn Yu2 1Department of Nursing, Yixing People’s Hospital, Yixing, Jiangsu, 214200, People’s Republic of China; 2Department of General Surgery, Yixing Traditional Chinese Medicine Hospital, Yixing, 214200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuequn Yu, Department of General Surgery, Yixing Traditional Chinese Medicine Hospital, Yixing, 214200, People’s Republic of China, Email zjw911@qq.comBackground: Research on rehabilitation in breast cancer (BC) patients is scarce. This study explored the knowledge, attitude, and practice (KAP) toward rehabilitation in BC patients who underwent surgery.Methods: This cross-sectional survey study was conducted between August 2022 and February 2023 in eight hospitals in Yixing City, Jiangsu Province. An investigator-designed survey was used to evaluate the participants’ KAP toward BC rehabilitation.Results: The analysis included 578 valid surveys. The participants displayed good knowledge, positive attitudes, and proactive practice toward rehabilitation after surgery for BC. The multivariable logistic regression analysis showed that the knowledge scores and attitude scores were independently and positively associated with proactive practice, while age 45– 55, age 56– 60, ≥ 6 years BC duration, modified radical surgery, and radical surgery were independently and negatively associated with proactive practice (all P < 0.05). The structural equation model revealed a positive direct effect of knowledge on both attitude and practice. In addition, attitudes had a positive direct influence on practice.Conclusion: Patients with BC exhibited favorable KAP rehabilitation after surgery for BC, but targeted education could be needed to enhance specific points of understanding and reinforce proactive engagement in clinical practice.Keywords: breast cancer, knowledge, attitude, practice, rehabilitation, cross-sectional study